Online consumer protection : theories of human relativism - Chen, Kuanchin; Fadlalla, Adam (Hershey, PA : Information Science Reference, 2009)
'This book is designed to offer readers a comprehensive way to understand the nature of online threats, consumer concerns, and techniques for online privacy protection'--Provided by publisher
'Premier reference source'--Cover
Includes bibliographical references (p. 388-428) and index
Keywords: Consumer protection; Ethical relativism; Electronic commerce -- Security measures; Electronic information resources -- Access control; Disclosure of information; Privacy, Right of; Computer crimes